KAJIAN KERUSAKAN DAN KERUNTUHAN TUBUH BENDUNG AKIBAT PENGARUH BANJIR (STUDI KASUS : BENDUNG CIPAMINGKIS KAB. BOGOR) - Heri Suherlan (TECHNO-SOCIO EKONOMIKA, 2021)
Land use in the vicinity of Cipamingkis Sub-watershed is currently very intensive, so that damage to land which is feared has an impact on the level of fertility and carrying capacity of the land, resulting in the danger of flooding, erosion and landslides in the rainy season, as well as a decrease in water discharge and lack of groundwater in the season dry. The impact of these conditions Cipamingkis Weir in Sukasirna Village, Jonggol District on April 20, 2017 there was a breakdown of the lighthouse and the body of the weir which was built since 1982, the dam irrigated 4579 Ha of rice fields, unable to irrigate and in the lower reaches of the dam a lot of damage, including: eroded riverbanks, damaged river cliffs, and part of the land cracked and landslides.Seeing the condition needs to be made a research on Cipamingkis Dam Damage Study. This handling is urgently needed to reduce and reduce the consequences caused in the process of activities that cause erosion and flooding.